A study to assess the effectiveness of planned teaching programme on knowledge regarding effects of junk foods on health among adolescents in selected high schools of Srinagar - Yousuf, Andleeb (International Journal of Nursing Research, 2023)
“Junk food" generally refers to foods that contain lot of calories with little nutritional value. Adolescents suddenly seem to have stepped into a world of fast food and vending machines, totally unaware of havoc they are creating for themselves. Adolescents are at greater risk for nutritional problem both from physiological and psychological standpoint. Most of the adolescents have little knowledge about health hazards of junk foods. Aim: Aim of the study was to enhance knowledge of adolescents regarding effects of junk foods on health and in turn to reduce the incidence of consumption of junk foods by adopting healthier eating habits. Materials and methods: A pre- experimental study was conducted using one group pre- test, post -test design to assess the level of knowledge regarding effects of junk foods on health. The study was conducted in 2 selected schools of Srinagar (Radiant public school and Kashani memorial school). The sample was selected by Stratified simple random sampling. The sample size was 80. Structured questionnaire was used to assess the knowledge of adolescents. Results: The overall mean knowledge score 25.91 obtained by the subjects in post- test was higher than mean knowledge score 16.90 in the pre -test and with the improvement score as 9.01. There was significant difference between pre-test and post-test knowledge score at p<0.05. The results of the study revealed that the planned teaching program was significantly effective in improving the knowledge of adolescents. Conclusion: Hence, the study concluded that improved knowledge regarding health hazards of junk foods helps the adolescents to avoid junk foods and adopt healthy eating habits.